2005
DOI: 10.2174/138527205774610903
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Reactivity and Catalytic Effects of Copper(II) Halides in Organic Syntheses

Abstract: Copper(II) salts are widely applied for the halogenation of aromatic and heteroaromatic systems, the halides. In coupling reactions, CuCl 2 has been used as a catalyst for the benzylation of aromates, the synthesis of alkanes, and the preparation of diacetylenes, cyclohexenones and symmetric biaryls. It has further proved suitable for stereoselective cyclization to lactones, carbon-nitrogen coupling and lactamization, and for the simple preparation of aroylaminohydrazones, the allylic amination of olefins, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 106 publications
0
7
0
Order By: Relevance
“…93 The nature of the base required for the selective formation of the 3-acyloxy regioisomer supported possible involvement of allene intermediate 37, which is generated upon initial prototropic rearrangement of the substrate. Based on further mechanistic studies involving 17 O-labeled substrates, we proposed that this formal 1,2-acyloxy-group migration 94,95 likely occurs through the involvement of a dioxolenylium intermediate. 96 …”
Section: Synthesis Of Heterocycles Via Migratory Cycloisomerizationsmentioning
confidence: 99%
“…93 The nature of the base required for the selective formation of the 3-acyloxy regioisomer supported possible involvement of allene intermediate 37, which is generated upon initial prototropic rearrangement of the substrate. Based on further mechanistic studies involving 17 O-labeled substrates, we proposed that this formal 1,2-acyloxy-group migration 94,95 likely occurs through the involvement of a dioxolenylium intermediate. 96 …”
Section: Synthesis Of Heterocycles Via Migratory Cycloisomerizationsmentioning
confidence: 99%
“…302 Later, it was found that Cu(I)- or Cu(II)-salts were equally efficient in this transformation. 303 It was shown that di-, tri-, and tetrasubstituted pyrroles 3-29 with different substitution patterns could readily be synthesized using this method (Scheme 182). It should be noted that in the case of substrates 3-28 bearing terminal alkyne (R 4 = H), a spontaneous cycloisomerization was observed.…”
Section: Synthesis Of Pyrrolesmentioning
confidence: 99%
“…The bromination of the ligands is not surprising as CuBr 2 is an effective reagent for the bromination of activated aromatics. 28,29 The aryl bromination reaction produces cuprous bromide and hydrogen bromide as side-products (according to: Ar-H + 2CuBr 2 ¼ Ar-Br + H-Br + 2CuBr). However, rather surprisingly bromination of the ligand (L 2 ) did not take place in the case of complex 2 indicating that substitution of the H-atom of the aldehyde by a methyl group prevents the ligand from bromination i.e.…”
Section: Description Of Structures Of Complexes 1 Andmentioning
confidence: 99%